Biopsychosocial Contributors to Parent Behaviors during Child Venipuncture - Kaytlin L. Constantin; Rachel L. Moline; Rebecca Pillai Riddell; Jeffrey R. Spence; C. Meghan McMurtry (MDPI AG, 2022)
Children's needle-related distress is strongly related to parental verbal behaviors. Yet, empirical data supporting theorized contributors to parent behaviors in this context remain limited. This is the first study to collectively measure biological (heart rate variability; HRV), psychological (catastrophizing, anxiety), and social (child behaviors) contributors to parent verbal behaviors throughout pediatric venipuncture. HRV was used as a measure of emotion regulation capacity and examined as a moderator in the associations between parent psychological factors and their behaviors, and between child and parent behaviors. Sixty-one children aged 7 to 12 years who presented at an outpatient blood lab for venipuncture and a parent participated. Parent baseline HRV, state catastrophizing, and anxiety were measured prior to venipuncture. The procedure was video-recorded for later coding of pairs' verbal behaviors. Strong associations emerged between child behaviors and parent behaviors. Baseline HRV moderated the association between parent catastrophizing and behavior. Social factors remain a strong influence related to parent behaviors. Psychologically, parent negative cognitions differentially related to parent behaviors based on their emotion regulation capacity. Biologically, low baseline HRV may increase the risk that certain parents engage in a constellation of behaviors that simultaneously direct their child's attention toward the procedure and inadvertently communicate parental worry, fear, or concern.